Dream Work Pictures Sdn. Bhd. / Rosnani Taman ... [et al.] - Taman, Rosnani; Gubes, Danny; Micheal, Charles; Morinding, Farizi; Zakaria, Nazarudin; Mohd Kamal, Kamarul Halmi; Shariff Abd Aziz, Shariff Munawar (Faculty of Artistic and Creative Technology, 2003)
Dream Work pictures Sdn Bhd is a production house and service helping programs about MCP and all show television especially TV3 and NTV7. Dream Work Pictures is also excellent in every work about that undertaking and responsible for the action and commitment. We had provided services that will ensure to attract people to participate in each of our event. These are, I. To provided clients with and experience of great about TV programs and help them to enhance their performance in every aspect. II. In Malaysia through strategic networking in industry and establishing smart partnership with established institutions for the enrichment and accreditation purposes. III. To undertake entrepreneurial activities in a professional and business like manner.